Study Of Text, Cotext And Context In The Radar Madura Newspaper May 2024 Edition - Masudah; Roni Mainata Alam; Amirul Mukminin (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
This research aims to analyze the text, cotext and context of the May 2024 Edition of the Radar Madura Newspaper. This research uses a qualitative approach with descriptive methods. The data source used is the discourse contained in the May 2024 Edition of the Radar Madura Newspaper, entitled " Because of Uploading SARA Content, Creator of Akeloy Production Arrested by East Java Regional Police ", " Not Present at CAT, 14 PPK Applicants for Sampang Regional Election Fall Early ”, “ Laboratory Test Results Not Yet Out, Snack Samples That Trigger Mass Poisoning Sent to Surabaya ”. The results of this research from the three analyzed data found that there were three texts, five cotexts and six contexts in the May 2024 edition of the Radar Madura Newspaper.